A new species of the genus Euboeus Boieldieu, 1865 from Northern Iran (Coleoptera: Tenebrionidae: Helopini) - Mofrad, Farhad Eshraghi (Zootaxa, 2023)
A new tenebrionid species of the genus Euboeus Boieldieu, 1865, E. kandovanensis sp. n., is described from Alborz Province, Iran. It was collected in high mountains at an altitude of near 3.000 m. The new species belongs to the species-group huedepohli and the subgroup huedepohli within this group, which unites high mountain species with rugosity on the basal piece (dorsal surface) of the aedeagus. Euboeus kandovanensis sp. n. is most similar to E. huedepohli (Kulzer, 1964) and E. kasatkini Nabozhenko, 2022 and differs in the shape of the pronotum, the sculpture of the prothoracic hypomera, the structure of the metatibiae in both sexes, and the structure of the aedeagus.